2016
DOI: 10.1089/gtmb.2015.0195
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in Endothelial Nitric Oxide Synthesis and Renin–Angiotensin–Aldosterone System with Developing of Coronary Artery Disease in Bulgarian Patients

Abstract: The eNOS G894T and ACE I/D polymorphisms are associated with an increased risk of developing ACS after adjusting for classical risk factors for atherosclerosis in the Bulgarian cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…However, this relationship occurred for the TT genotype (P = 0.05) and the T allele (P = 0.014). Mokretar et al (2016) in a cohort study of Bulgarian patients presented a high percentage of T894 alleles in patients with coronary ischemia (N = 171) compared to the control group (N = 123) (P = 0.006). Antoniades et al (2005) in their studies with 229 patients who underwent AMI in the early age (before 55 years old) found the TT homozygous polymorphism for G894T with a significant difference, as well as Isordia-Salas et al (2009) who described Glu298ASP as an independent risk factor for early AMI.…”
Section: Discussionmentioning
confidence: 92%
“…However, this relationship occurred for the TT genotype (P = 0.05) and the T allele (P = 0.014). Mokretar et al (2016) in a cohort study of Bulgarian patients presented a high percentage of T894 alleles in patients with coronary ischemia (N = 171) compared to the control group (N = 123) (P = 0.006). Antoniades et al (2005) in their studies with 229 patients who underwent AMI in the early age (before 55 years old) found the TT homozygous polymorphism for G894T with a significant difference, as well as Isordia-Salas et al (2009) who described Glu298ASP as an independent risk factor for early AMI.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, L-arginine 9 g/d ameliorates symptomatic vasospastic angina among patients with Prinzmetal's angina 15,16 and L-citrulline 800 mg/d increases flowmediated dilation of the brachial artery among patients with vasospastic angina. 19 To the extent that nitric oxide plays an important etiologic role in osteonecrosis, 1,2,7,10-14 in a fashion similar to Prinzmetal's angina, [15][16][17][18][19] L-arginine or L-citrulline should be therapeutic for osteonecrosis, reducing arterial, arteriolar, and endothelial disease. Along with venous occlusion, this disease promotes primary osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of L-arginine 5 to 15 g/d restores physiologic levels of nitric oxide and augments nitric oxide-dependent signaling. 24 It is therapeutic for Prinzmetal's angina [15][16][17][18][19] and may be therapeutic for primary osteonecrosis if initiated before joint collapse occurs (Ficat stage I-II). 1,2,7,10-14…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that high ACE and angiotensinogen affect the structure and function arteries and the heart. The D allele of ACE was reported to influence plasma level and activity of the ACE enzyme, resulting in elevation of Ang-II sensitivity; this is believed to involve the interaction of MI/R, ventricular hypertrophy, and hypertension [35]. ECG elevation in patients is not the only parameter used to diagnose acute MI/R; it also has to be measured by a series of ECG for diagnosis.…”
Section: Discussionmentioning
confidence: 99%